THE RELATIONSHIP BETWEEN GADGET USE AND THE INCIDENCE OF MYOPIA AMONG HIGH SCHOOL STUDENTS DURING ONLINE LEARNING - Siska Febriyani; Siwi Sri Widhowati; Imam Purnomo (Indonesian Journal of Community Health Nursing, 2023)
Background. Online learning is a solution to inhibit the transmission of viruses during the COVID-19 pandemic. However, students can be exposed to prolonged use of gadgets which can cause myopia. This study aimed to determine the relationship between gadget use and the incidence of myopia in students at SMA Muhammadiyah 1 Pekajangan Pekalongan during online learning. Methods. This study was a correlational study with a cross-sectional approach. The sample was 121 students from grades XI and XII selected by convenience sampling technique. Data were obtained using an online questionnaire. Chi Square test was used in bivariate analysis. Binary logistic regression was used in multivariate analysis. Results. The incidence of myopia in SMA Muhammadiyah 1 Pekajangan Pekalongan was 43.8%. Students who used gadgets with a duration of > 6 hours were at risk of myopia by 9.733 times compared to students who used gadgets <= 6 hours (p-value 0.001). Compared to students who used gadgets with moderate light intensity, students who used gadgets with bright intensity had a 50.058 times greater risk (p-value 0.002), students who used gadgets with dim light intensity had a 6.861 times greater risk (p-value 0.015). Students who used gadgets with a distance < 30 cm had a risk of myopia of 15.030 times compared to students who used gadgets with a distance >= 30 cm (p-value 0.013). Conclusion. There is an association between gadget use (in terms of duration, light intensity, and distance) and the incidence of myopia, even after controlling for genetic factor.